Economic fluctuations and forecasting - Chambers, Edward J. (Englewood Cliffs, N.J., Prentice-Hall, 1961)
This book contains materials found in most standard works on economic fluctuations: types of fluctuations, the historical record and the evolution of fluctuation theory. The independence of cyclical and secular forces in shaping the nature of economic change was stressed. The book also looks at the role of economic forecasting and the alternative approaches that may be employed.
Includes bibliography.
oo 13/09/2018
Loans
Keywords: Business cycles; Economic forecasting; Economic stabilization